Peningkatan Skill Entrepreneur Bagi Siswa-Siswi SMAN 1 Sei Kepayang - Yuliana Dewi (CV. ITTC INDONESIA, 2025)
Community Service Activities (PPM) in the form of Youth Leadership Training for Mosques in Panca Arga Village, Rawang District. Panca Arga aims to provide knowledge about management, attitudes, leadership, especially the skills of youth of the Mosque, Mosque administrators, including Village government officials and all Village institutions as their working partners. The target audience in this Community Service (PPM) activity is youth of the Mosque, Mosque administrators, Village Government officials of Panca Arga Village, Rawang District. Panca Arga, totaling 50 people. This Youth Leadership Training for Mosques is carried out using lecture, demonstration and practice methods accompanied by questions and answers. The lecture method is used to explain the concept of coaching and theories about organizations and instilling the leadership character of youth of the Mosque. The demonstration method is used to show a work process, namely the development of youth leadership of the Mosque. While the practice method is to practice organizational management methods and leadership character. While the question and answer method is to provide participants with the opportunity to consult on organizational management such as organizational resource management and leadership. Availability of adequate experts in the Youth Leadership Training of Mosques in Panca Arga Village, Rawang District, Panca Arga in the Islamic Religious Education Study Program and other Study Programs, enthusiasm of participants, support from the Rector of IAIDU Asahan Kisaran for the implementation of activities and supporting funds for the implementation of this Community Service (PPM) activity. The obstacles faced are that many youth of the Mosque, Mosque administrators, still do not have initial knowledge about organizations and leadership.